Ahmad Domocao Alonto: (1914-2002): his contribution towards Islamic thought in the Philippines - Disomimba, Mohammad Nashief S.; Abdelaziz, Berghout; Ali, Kalsom (USIM Press, 2018)
Islamic thought in the Philippines has existed before the coming of Spaniards and has a very strong impact on Philippines sociopolitical affairs; very few studies have been conducted on individuals who have contributed to the Islamic thought in the Philippines. Tendency of giving priority wo well-known Muslim scholars predominates over those who whose works remain hidden and unexplored. To address this limitation, an analysis study is conceived to foreground a Muslim leader and intellectual in Mindanao, as a grand master of Islamic movements in the Philippines. Popularly known among his colleagues in the Philippine Senate in the 1950s as Domi, Ahmad Domocao Alonto, born on August, 1914 in Lanao del Sur, Mindanao, Philippines. He died on December 11th, at the age of 88, but his legacy lives on and his writings and works have survived. Ahmad Domocao Alonto is one of the 100 great Muslim leaders of the 20th century.